Carbonate-carbonate coupling on platinum surface promotes electrochemical water oxidation to hydrogen peroxide - Heng Zhu; Ximei Lv; Yuexu Wu; Wentao Wang; Yuping Wu; Shicheng Yan; Yuhui Chen (Nature Communications)
Abstract Water electro-oxidation to form H2O2 is an important way to produce H2O2 which is widely applied in industry. However, its mechanism is under debate and HO(ads), hydroxyl group adsorbed onto the surface of the electrode, is regarded as an important intermediate. Herein, we study the mechanism of water oxidation to H2O2 at Pt electrode using in-situ Raman spectroscopy and differential electrochemical mass spectroscopy and find peroxide bond mainly originated from the coupling of two CO3 2- via a C2O6 2- intermediate. By quantifying the 18O isotope in the product, we find that 93% of H2O2 was formed via the CO3 2- coupling route and 7% of H2O2 is from OH(ads)-CO3 •− route. The OH(ads)-OH(ads) coupling route has a negligible contribution. The comparison of various electrodes shows that the strong adsorption of CO3(ads) at the electrode surface is essential. Combining with a commercial cathode catalyst to produce H2O2 during oxygen reduction, we assemble a flow cell in which the cathode and anode simultaneously produce H2O2. It shows a Faradaic efficiency of 150% of H2O2 at 1 A cm−2 with a cell voltage of 2.3 V.